Dissemination and consensual perceptions of nation brands: a framework for future research. Issue 1 (11th December 2019) - Torelli, Carlos J.
Abstract : Purpose: The purpose of this paper is to comment on the article by He et al., and to propose a framework for the worldwide dissemination of a nation brand image as a way to understand the nature and resilience of nation brands. Design/methodology/approach: The approach is conceptual with illustrative examples. Findings: By integrating research on the dissemination of cultural narratives in a power structure with the literature on shared reality and consensual perceptions, this paper develops a framework for future research on the factors that impact the emergence of a consensual image about a nation brand. These factors include the nation's political and economic power, the widespread adoption of the nation's language and the nation's cultural attractiveness. The framework further proposes that these factors positively affect the likelihood that people would develop an image of what they perceive is widely shared about a nation brand, or the shared reality about the image of such nation brand. The framework also elaborates on some of the consequences for perpetuating the nation brand image and for reinforcing brand-affiliative consumption behaviors. Practical implications: This paper offers a framework that allows marketers to further understand the worldwide dissemination of nation brands. Originality/value: The paper integrates a novel framework with recent findings about the psychology of globalization, opening avenues for future research on nation branding.